2018
DOI: 10.3389/fphys.2018.01549
|View full text |Cite
|
Sign up to set email alerts
|

Association Between c-Myc and Colorectal Cancer Prognosis: A Meta-Analysis

Abstract: Background: There is debate as to whether c-Myc predicts prognosis in colorectal cancer (CRC). In this study, we aimed to review the association between c-Myc and CRC prognosis.Methods: Pertinent studies were identified by searching electronic databases and carefully reviewing the reference lists of pertinent studies until March 2016. The summary hazard ratio (HR) and corresponding 95% confidence interval (CI) were calculated to study the association between c-Myc and CRC prognosis.Results: Eight cohort studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
1
24
1
Order By: Relevance
“…Although a recent consensus molecular analysis individuated the c-MYC alteration as a specific marker of a particular CRC sub-group (the CMS2 subtype), definitively confirming the involvement of c-MYC in the CRC pathogenesis, the same study did not find a significant association of this group to a better or worse OS or PFS [23,24]. Similarly, several works and meta-analyses of public databases (also including the TCGA database) seem to strengthen the controversial prognostic value of c-MYC in CRC [25]. Probably, the multi-variegate treatments, the methodological analysis of c-MYC expression based on the mRNA levels and the clinical inhomogeneity of the analyzed cohorts could play a role in these results [23][24][25].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Although a recent consensus molecular analysis individuated the c-MYC alteration as a specific marker of a particular CRC sub-group (the CMS2 subtype), definitively confirming the involvement of c-MYC in the CRC pathogenesis, the same study did not find a significant association of this group to a better or worse OS or PFS [23,24]. Similarly, several works and meta-analyses of public databases (also including the TCGA database) seem to strengthen the controversial prognostic value of c-MYC in CRC [25]. Probably, the multi-variegate treatments, the methodological analysis of c-MYC expression based on the mRNA levels and the clinical inhomogeneity of the analyzed cohorts could play a role in these results [23][24][25].…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, several works and meta-analyses of public databases (also including the TCGA database) seem to strengthen the controversial prognostic value of c-MYC in CRC [25]. Probably, the multi-variegate treatments, the methodological analysis of c-MYC expression based on the mRNA levels and the clinical inhomogeneity of the analyzed cohorts could play a role in these results [23][24][25].…”
Section: Discussionmentioning
confidence: 94%
“…Several studies displayed significant association between the overexpression of c-Myc and poor prognosis in numerous tumors, while other studies revealed an opposite correlation. On the contrary, some reports did not support either of these conclusions (Zaharieva et al, 2005;Tsiatis et al, 2009;Massari et al, 2015;Zeng et al, 2015;Strindlund et al, 2017;He et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…Aberrant expression of MYC is observed in many human cancers including CRC 11 , but the prognostic value of MYC in CRC remains debatable. A recent report using a meta-analysis shows that MYC is not significantly associated with CRC prognosis 57 . We found that MYC expression is significantly and positively associated with SMS expression in CRC, although SMS expression is not regulated by MYC.…”
Section: Discussionmentioning
confidence: 99%